Impact of Artocarpus lakoocha heartwood extract and Oxyresveratrol on cholesterol digestion and absorption in Caco-2 cell cultures - Kanittaporn Trisat, Nanteetip Limpeanchob (Journal of Applied Pharmaceutical Science, 2025)
Cardiovascular diseases are the leading causes of death globally, with hypercholesterolemia being a major contributing factor. While lifestyle changes and dietary modifications are recommended for individuals with moderately high cholesterol, there is growing interest in natural alternatives to help manage blood cholesterol levels. Oxyresveratrol has shown promising antihyperlipidemic properties in animal studies. However, the mechanisms underlying these effects are not fully understood. This study focuses on the direct effects of oxyresveratrol and Puag-Haad, an aqueous extract from the heartwood of Artocarpus lakoocha, on lipid and cholesterol processing in the intestinal tract. The study assessed the inhibitory effects on pancreatic lipase, solubility of cholesterol in lipid micelles, bile acid binding, and absorption of cholesterol into differentiated Caco-2 cells. The results showed that both oxyresveratrol and Puag-Haad exhibited a dose-dependent inhibition of pancreatic lipase. Both compounds also effectively inhibited cholesterol solubility in lipid micelles. Puag-Haad in particular bound to bile acids with higher potency than the standard bile acid binder, cholestyramine. In addition, oxyresveratrol and Puag-Haad inhibited cholesterol uptake into Caco-2 intestinal cells, with efficacy comparable to the cholesterol absorption inhibitor ezetimibe. These findings indicate that oxyresveratrol and Puag-Haad interfere with multiple processes involved in lipid digestion and absorption, making them promising candidates for further development as natural antihyperlipidemic agents.
Keywords: Oxyresveratrol, Artocarpus lakoocha, Puag-Haad, cholesterol absorption, Caco-2 cell